Anti-LID effect back contact battery and preparation method thereof
By using continuous coating process and gradient oxidation treatment in the back contact battery, a dense oxide layer and a phosphorus-doped oxygen-doped amorphous silicon layer are formed, which solves the efficiency attenuation problem of the back contact battery under the LID effect, and improves the anti-attenuation performance and passivation level of the battery.
Patent Information
- Application Number
- CN202510919222.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2045-07-04
AI Technical Summary
The existing back contact batteries have severe efficiency attenuation under the photoinduced attenuation (LID) effect, and the film layer is poor, so they cannot take into account both the battery's anti-LID effect performance and battery efficiency.
A continuous coating process is adopted to form a dense oxide layer and a phosphorus-doped oxygen-doped amorphous silicon layer on the backlight surface of the silicon wafer, combined with ozone flow gradient incremental oxidation and hydrogen plasma treatment, to form a dense oxide layer to prevent phosphorus penetration, and to increase the film layer binding force through continuous gradient doping, and to form a carbon-doped silicon nitride anti-reverse layer with continuous coating to improve passivation level and battery efficiency.
The anti-LID attenuation performance and overall passivation level of the back contact battery are improved, the density of the film layer and battery efficiency are enhanced, the waiting time during the coating process is reduced, and the utilization rate of the equipment is improved.
Smart Images

Figure CN120417549A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of back-contact batteries, and particularly relates to a back-contact battery with anti-LID effect and a preparation method thereof. Background Art
[0002] At present, the manufacturing of back-contact batteries with relatively low equipment costs adopts a post-etching process. The photoelectric conversion efficiency (also known as the battery efficiency) of existing back-contact batteries has been gradually improved. While achieving high conversion efficiency, it is also necessary to consider how to ensure that the battery still maintains high conversion efficiency under actual outdoor working conditions. Therefore, in addition to conversion efficiency, reliability has also become a key factor in measuring the quality of crystalline silicon solar cells and modules. LID, namely light-induced degradation, is one of the indicators for testing the reliability of solar cells. The phenomenon of LID is that when the battery is irradiated under sunlight, the power generation power, short-circuit current, open-circuit voltage, etc. of the battery will exponentially decay and reach a stable state after 12 hours of irradiation. At present, there is a certain LID situation in back-contact batteries, and there is an urgent need for a back-contact battery with anti-LID effect. However, in existing back-contact batteries, the conventional film layers generally adopt film layers with different gradient changes of doping elements. This film layer usually adopts the PECVD coating method, and the process gas pressure curve in the coating process is as Figure 1 shown, specifically: The first gradient corresponds to the film thickness: stable inlet pressure - glow coating - evacuation after glow coating ends; The second gradient corresponds to the film thickness: re-inlet stable pressure - glow coating - evacuation after glow coating ends; The third gradient corresponds to the film thickness: repeat the above steps. In this way, the gases between different gradient film layers can not interfere with each other, and it has good battery efficiency. However, because there are inflation and evacuation actions between each film layer, there is a waiting time, and the surface of the film layer is prone to oxidation due to the high-temperature waiting for the inlet of special gas. Defects such as weak bonding force between silicon-silicon bonds or silicon-hydrogen bonds between different gradient film layers result in poor film layer quality and poor LID performance.
[0003] It should be noted that this part of the content of the present invention only provides background technology related to the present invention, and does not necessarily constitute prior art or well-known technology. Summary of the Invention
[0004] The purpose of the present invention is to overcome the defect that existing back-contact batteries in the prior art cannot simultaneously take into account the anti-LID effect performance and battery efficiency of the battery, and provide a back-contact battery with anti-LID effect and a preparation method thereof, which can improve the anti-LID attenuation performance of the battery, and at the same time effectively improve the overall passivation level and battery efficiency.
[0005] To achieve the above object, in a first aspect, the present invention provides a method for preparing a back-contact battery resistant to the LID effect, comprising: forming a first semiconductor layer on the backlight side of a silicon wafer, and then etching the first semiconductor layer to form second semiconductor opening regions distributed at intervals; then performing texturing cleaning to form a textured surface on the light-receiving side of the silicon wafer and the second semiconductor opening regions; then sequentially forming a passivation layer and an antireflection layer on the light-receiving side of the silicon wafer, the passivation layer comprising a dense oxide layer and a phosphorus-doped and oxygen-doped amorphous silicon layer formed in sequence; Among them, the formation of the dense oxide layer includes the steps of first performing ozone flow gradient-increasing oxidation and then performing hydrogen plasma treatment; The formation of the phosphorus-doped and oxygen-doped amorphous silicon layer includes the step of continuously depositing at least one of the gases in the gas introduced under the continuous presence of glow plasma with a gradient change, and the at least one gradient change in the gas introduced here causes the phosphorus doping concentration in the phosphorus-doped and oxygen-doped amorphous silicon layer to gradually increase from the inside to the outside.
[0006] In some preferred embodiments of the present invention, the thickness of the dense oxide layer is 0.5 - 2.5 nm, and the thickness of the phosphorus-doped and oxygen-doped amorphous silicon layer is 3 - 15 nm.
[0007] In some preferred embodiments of the present invention, the thickness ratio of the dense oxide layer to the phosphorus-doped and oxygen-doped amorphous silicon layer is (0.03 - 0.83):1.
[0008] In some preferred embodiments of the present invention, in the dense oxide layer, the ozone flow gradient-increasing oxidation adopts atomic layer deposition, and the oxidation temperature is controlled to be 150 - 300 °C.
[0009] In some preferred embodiments of the present invention, in the dense oxide layer, the hydrogen plasma treatment adopts tube-type PECVD, and the treatment temperature of the hydrogen plasma treatment is controlled to be 350 - 600 °C.
[0010] In some preferred embodiments of the present invention, the ozone flow gradient-increasing in the formation of the dense oxide layer includes at least three gradient-increasings: the ozone flow F1 in the first gradient is 1000 sccm - 3000 sccm, the ozone flow F2 in the second gradient is 3000 sccm - 5000 sccm, the ozone flow F3 in the third gradient is 4000 sccm - 6000 sccm, and F1 < F2 < F3.
[0011] In some preferred embodiments of the present invention, the ozone introduction time in the first gradient is 5 - 10 s, the ozone introduction time in the second gradient is 10 - 15 s, and the ozone introduction time in the third gradient is 10 - 15 s.
[0012] In some preferred embodiments of the present invention, the ozone flow gradient-increasing in the formation of the dense oxide layer further includes: purging the chamber and pipeline with nitrogen after the corresponding oxidation in each gradient.
[0013] In some preferred embodiments of the present invention, the conditions for hydrogen plasma treatment include: The flow rate of hydrogen is 5000 - 15000 sccm, and the treatment time is 5 - 60 s; and / or, The deposition pressure is 1300 - 2500 mtorr, and the power is 5 kw - 20 kw.
[0014] In some preferred embodiments of the present invention, the formation of the phosphorus - and oxygen - doped amorphous silicon layer is carried out by tube - type PECVD. Among them, the deposition temperature is controlled at 350 - 600 °C; and / or, the deposition pressure is controlled at 1300 - 2500 mtorr and the power is 5 kw - 20 kw.
[0015] In some preferred embodiments of the present invention, the gases introduced during the formation of the phosphorus - and oxygen - doped amorphous silicon layer include silane, a hydrogen mixture carrying phosphine, and nitrous oxide. The flow rate of silane is 800 - 2000 sccm, the flow rate of the hydrogen mixture carrying phosphine is 50 - 1000 sccm, and the flow rate of nitrous oxide is 100 - 2500 sccm.
[0016] In some preferred embodiments of the present invention, during the formation of the phosphorus - and oxygen - doped amorphous silicon layer, the flow rates of silane and nitrous oxide are kept constant, and the flow rate of the hydrogen mixture carrying phosphine changes in a gradient and increases, and the increasing amplitude is 50 - 200 sccm; among them, The number of gradient changes is at least 3 times, and / or the flow rate of the hydrogen mixture carrying phosphine is changed to the corresponding gradient change value every time 0.5 - 2 nm thickness is deposited.
[0017] In some preferred embodiments of the present invention, the phosphorus doping concentration range in the phosphorus - and oxygen - doped amorphous silicon layer is 1×10 19 cm -3 -9×10 20 cm -3 , and the oxygen doping concentration range is 1×10 18 cm -3 -9×10 19 cm -3 .
[0018] In some preferred embodiments of the present invention, the antireflection layer is at least one of silicon nitride, oxygen - doped silicon nitride, and carbon - doped silicon nitride.
[0019] In some preferred embodiments of the present invention, the antireflection layer includes carbon - doped silicon nitride. The formation of carbon - doped silicon nitride includes a step of continuously coating by at least one gradient change of the gases introduced in the continuous presence of glow plasma, and at least one gradient change of the gases introduced here makes the refractive index of carbon - doped silicon nitride gradually decrease from the inside to the outside.
[0020] In some preferred embodiments of the present invention, the carbon doping concentration in carbon-doped silicon nitride is 1×10 19 cm -3 -9×10 21 cm -3 , and the nitrogen doping concentration is 1×10 19 cm -3 -9×10 21 cm -3 ; and / or, the refractive index change range of the carbon-doped silicon nitride is 1.5 - 2.1.
[0021] In some preferred embodiments of the present invention, the carbon-doped silicon nitride is deposited by a tube-type PECVD method, and the deposition conditions include: controlling the deposition temperature to be 350 - 600 °C, the deposition pressure to be 1300 - 2500 mtorr, and the power to be 5 kw - 20 kw.
[0022] In some preferred embodiments of the present invention, the gases introduced during the formation of the carbon-doped silicon nitride include silane, ammonia, and methane. The flow rate of silane is 800 - 2000 sccm, the flow rate of ammonia is 6000 - 15000 sccm, and the flow rate of methane is 20 - 1000 sccm, preferably 100 - 1000 sccm.
[0023] In some preferred embodiments of the present invention, the gases introduced during the formation of the carbon-doped silicon nitride include silane, ammonia, and methane. During this process, the flow rate of silane is controlled to be constant, and the flow rates of ammonia and methane change in gradients respectively and satisfy: The flow rates of ammonia and methane change once every deposition of 20 - 40 nm thickness. The increasing change range of the ammonia flow rate is 1000 - 2000 sccm, and the increasing change range of the methane flow rate is 50 - 150 sccm; and / or, The initial flow rate range of ammonia is 6000 - 8000 sccm, and the initial flow rate range of methane is 0 - 100 sccm.
[0024] In some preferred embodiments of the present invention, the thickness of the carbon-doped silicon nitride is 80 - 160 nm, and / or, the thickness ratio of the carbon-doped silicon nitride to the phosphorus-doped and oxygen-doped amorphous silicon layer is (5.3 - 53.3):1.
[0025] In some preferred embodiments of the present invention, the preparation method further includes: After forming the first semiconductor layer on the backlight side of the silicon wafer, a mask layer is further formed, and then the second semiconductor opening region is formed; and in the final cleaning step of the texturing cleaning, it is selected whether to remove the mask layer outside the second semiconductor opening region on the backlight side of the silicon wafer according to requirements; After forming the antireflection layer, the second semiconductor opening region is cleaned; Then, a second semiconductor layer is deposited on the back surface; A second etching opening is performed on a part of the second semiconductor layer on the back surface of the silicon wafer to form a first semiconductor opening region arranged at intervals with the second semiconductor opening region; A conductive film layer is deposited on the obtained back surface; A third etching opening is performed on a part of the conductive film layer located between the first semiconductor opening region and the second semiconductor opening region to form an isolation groove; Metal electrodes are respectively formed on the outer surfaces of the conductive film layers corresponding to the regions where the first semiconductor opening region and the second semiconductor opening region are located; Wherein, the first semiconductor layer includes a first passivation layer and a first doped silicon layer arranged in sequence, the second semiconductor layer includes a second passivation layer and a second doped silicon layer arranged in sequence, the first passivation layer and the second passivation layer are independently a tunneling oxide layer or an intrinsic silicon layer, and the first doped silicon layer and the second doped silicon layer are independently polycrystalline silicon, amorphous silicon or microcrystalline silicon.
[0026] In a second aspect, the present invention provides a back contact battery resistant to LID effect, which is obtained by the preparation method of the back contact battery resistant to LID effect described in the first aspect.
[0027] Beneficial effects: Through the above technical solutions, especially in the post-texturing method, a continuously deposited phosphorus-doped and oxygen-doped amorphous silicon layer with gradually increasing phosphorus doping is formed by continuous coating using sustained glow plasma. In this continuous coating method of the phosphorus-doped and oxygen-doped amorphous silicon layer, there is no need to evacuate the gas between layers with different gradients, and the glow plasma does not need to be interrupted, resulting in a natural transition state between the film thicknesses corresponding to different gradients. The bonding force between the bonds corresponding to different gradients is good, the film layer quality is better, and it has better LID attenuation resistance performance. By adopting the method of gradually increasing phosphorus doping during continuous coating, it is beneficial to improve the bonding force between bonds in the film layer, improve the compactness of the film layer, and further enhance the LID attenuation resistance performance of the battery. At the same time, due to continuous coating without interruption, a relatively high energy is accumulated between film layers with different gradients. Phosphorus atoms doped in the film layer may partially migrate to bulk silicon (i.e., the silicon wafer) as the temperature increases, damaging the interface passivation and generating a relatively high density of interface states. Therefore, the present invention also adopts the steps of first oxidizing with an increasing ozone flow gradient and then performing hydrogen plasma treatment to form a dense oxide layer, which can effectively block the infiltration of phosphorus, and can effectively improve the overall passivation level and battery efficiency while maintaining good LID attenuation resistance performance of the battery. Among them, for the oxidation with an increasing ozone flow gradient, the ozone flow becomes larger and the oxidation degree becomes more sufficient, which is beneficial to forming a dense film layer. Through hydrogen plasma treatment, silicon and oxygen dangling bonds with a large number of defects on the surface of the silicon wafer's textured surface are removed, and a dense silicon surface oxide layer is retained, which is beneficial to improving the passivation level of subsequent film layers and effectively blocking the infiltration of phosphorus in the phosphorus-doped and oxygen-doped amorphous silicon layer, and can greatly improve the overall passivation level. Without a dense oxide layer, phosphorus in the phosphorus-doped and oxygen-doped amorphous silicon layer may migrate to the surface of the silicon wafer during deposition, resulting in serious carrier recombination and a significant decrease in passivation performance. At the same time, the passivation layer process can also well passivate the textured surface on the back, effectively reducing the density of interface defect states on the textured surface, thereby synergistically improving the passivation effects on both the front and back surfaces.
[0028] Among them, the continuous coating under the condition of sustained glow plasma refers to continuous glow deposition between the film thicknesses corresponding to different gradients in a single chamber, such as Figure 2 [[ID=z5]]shown. Compared with the Figure 1 conventional process, in the present invention, there is no evacuation in the middle, the glow plasma does not need to be interrupted, and the gas is continuously coated without stopping the glow to replace the gas, resulting in a natural transition state between the film thicknesses corresponding to different gradients. The energy between layers with different gradients accumulates gradually, the bonding force between the bonds of different gradient film layers is good, and the film layer quality is better. It not only enables the battery to have better LID attenuation resistance performance, but also reduces the operations of multiple evacuations and inflations during the coating process, shortens the coating cycle time to a certain extent, and is beneficial to improving the utilization rate of the equipment. At the same time, the present invention sets a continuously gradient-doped film layer. Because the doping concentration needs to be continuous, the gas flow rate of the doping gas needs to gradually increase continuously, so there is no interference problem between different gases.
[0029] In a preferred embodiment of the present invention, the anti-reflection layer is made of carbon-doped silicon nitride deposited continuously, which is beneficial to improving the density of the film layer, the anti-corrosion performance and the optical performance of the battery. At the same time, in combination with a specific passivation layer, the battery efficiency is further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention, and thus should not be regarded as limiting the scope. For those of ordinary skill in the art, without creative efforts, other related drawings can also be obtained based on these drawings.
[0031] Figure 1 is a coating process curve diagram of a PECVD-deposited multi-layer film of a conventional passivation layer.
[0032] Figure 2 is a coating process curve diagram of a PECVD-deposited film of a phosphorus- and oxygen-doped amorphous silicon layer of the passivation layer of the present invention.
[0033] Figure 3 is a schematic structural diagram of a specific embodiment of the back-contact battery of the present invention.
[0034] DESCRIPTION OF THE REFERENCE NUMERALS Silicon wafer 1, tunneling oxide layer 2, N-type doped polysilicon layer 3, dense oxide layer 51, phosphorus- and oxygen-doped amorphous silicon layer 52, anti-reflection layer 6, intrinsic hydrogenated amorphous silicon layer 7, P-type doped amorphous silicon layer 8, transparent conductive film layer 9, metal electrode 10. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0035] In the present invention, the terms "first" and "second" are only used for descriptive purposes and cannot be construed as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, the features defined with "first" and "second" may explicitly or implicitly include one or more of such features. In the description of the present invention, "a plurality of" means two or more unless otherwise specifically defined.
[0036] In the present invention, unless otherwise clearly specified and defined, the first feature being "on" or "under" the second feature may be that the first and second features are in direct contact, or the first and second features are indirectly in contact through an intermediate medium. Moreover, the first feature being "above", "over" and "on top of" the second feature may be that the first feature is directly above or obliquely above the second feature, or merely indicates that the first feature has a higher horizontal height than the second feature. The first feature being "under", "below" and "beneath" the second feature may be that the first feature is directly below or obliquely below the second feature, or merely indicates that the first feature has a lower horizontal height than the second feature.
[0037] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined to form one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein. The terms "optional" and "optional" both mean that a range may or may not be included (or may or may not be present).
[0038] In the present invention, the area close to the silicon wafer is considered as the inside, and the area far from the silicon wafer is considered as the outside.
[0039] In a first aspect, the present invention provides a method for preparing a back-contact battery with resistance to LID effect, comprising: forming a first semiconductor layer on the backlight surface of a silicon wafer, then etching the first semiconductor layer to form a second semiconductor opening area with spaced distributions; then performing texturing and cleaning to form a texturing surface on the light-receiving surface of the silicon wafer and the second semiconductor opening area; then forming a passivation layer and an anti-reflection layer in sequence on the light-receiving surface of the silicon wafer, the passivation layer comprising a dense oxide layer and a phosphorus-doped and oxygen-doped amorphous silicon layer formed in sequence.
[0040] The formation of the dense oxide layer includes the steps of first oxidizing with an ozone flow gradient increase and then performing hydrogen plasma treatment.
[0041] The formation of the phosphorus-doped and oxygen-doped amorphous silicon layer includes the steps of continuously coating by introducing at least one gradient change in the gas under the continuous presence of glow plasma, wherein the at least one gradient change in the gas introduced here causes the phosphorus doping concentration in the phosphorus-doped and oxygen-doped amorphous silicon layer to gradually increase from the inside to the outside.
[0042] In some preferred embodiments of the present invention, the thickness of the dense oxide layer is 0.5-2.5 nm.
[0043] Preferably, in the present invention, the thickness of the phosphorus-doped and oxygen-doped amorphous silicon layer is 3-15nm, for example, it can be 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, etc., and the range between any two point values, more preferably 3-10nm.
[0044] In some preferred embodiments of the present invention, the thickness ratios of the dense oxide layer and the phosphorus- and oxygen-doped amorphous silicon layer are (0.03-0.83):1 and (0.080-0.830):1. Using a dense oxide layer and phosphorus- and oxygen-doped amorphous silicon layer with an appropriate thickness ratio further enhances the passivation effect and prevents phosphorus from penetrating into the bulk silicon.
[0045] In some preferred embodiments of the present invention, in the dense oxide layer, the ozone flow gradient increasing oxidation adopts atomic layer deposition. More preferably, the ozone oxidation temperature is controlled at 150 - 300 °C.
[0046] In some preferred embodiments of the present invention, in the dense oxide layer, the hydrogen plasma treatment adopts tube PECVD. More preferably, the treatment temperature of the hydrogen plasma treatment is controlled at 350 - 600 °C.
[0047] In some preferred embodiments of the present invention, the ozone flow gradient increasing in the formation of the dense oxide layer includes at least three gradient increases: the ozone flow F1 in the first gradient is 1000 sccm - 3000 sccm, the ozone flow F2 in the second gradient is 3000 sccm - 5000 sccm, the ozone flow F3 in the third gradient is 4000 sccm - 6000 sccm, and F1 < F2 < F3. In this preferred scheme, the ozone flow increases appropriately in gradient, and the oxidation degree is more and more sufficient, which is more conducive to improving the optimal distribution of the film layer density, thus facilitating the improvement of the uniformity of oxidation between the edge and the middle of the silicon wafer, and more conducive to the improvement of battery performance.
[0048] In some preferred embodiments of the present invention, the ozone introduction time in the first gradient is 5 - 10 s, the ozone introduction time in the second gradient is 10 - 15 s, and the ozone introduction time in the third gradient is 10 - 15 s. More preferably, the ozone introduction times in the first gradient, the second gradient, and the third gradient increase gradually, which is more conducive to improving the density of oxidation.
[0049] In some preferred embodiments of the present invention, the ozone flow gradient increasing in the formation of the dense oxide layer further includes: after the corresponding oxidation in each gradient, the chamber and pipeline are purged with nitrogen, which is more conducive to improving the stability of gas supply and the density of oxidation. In a specific embodiment, the purging of the chamber and pipeline with nitrogen after the corresponding oxidation in each gradient includes: purging the chamber and pipeline with nitrogen after the ozone oxidation in the first gradient, purging the chamber and pipeline with nitrogen after the ozone oxidation in the second gradient, and purging the chamber and pipeline with nitrogen after the ozone oxidation in the third gradient.
[0050] In some preferred embodiments of the present invention, the conditions of the hydrogen plasma treatment include: the flow rate of hydrogen is 5000 - 15000 sccm, and the treatment time is 5 - 60 s. Adopting the hydrogen plasma treatment under appropriate conditions is more conducive to forming a dense surface state of the oxide layer.
[0051] In some preferred embodiments of the present invention, the conditions of the hydrogen plasma treatment include: the deposition pressure is 1300 - 2500 mtorr, and the power is 5 kw - 20 kw.
[0052] In some preferred embodiments of the present invention, the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer is carried out by a tube-type PECVD method. More preferably, the deposition temperature is controlled to be 350 - 600 °C.
[0053] In some preferred embodiments of the present invention, in the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer, the deposition pressure is controlled to be 1300 - 2500 mtorr and the power is 5 kW - 20 kW.
[0054] In some preferred embodiments of the present invention, the gases introduced in the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer include silane, a hydrogen gas mixture carrying phosphine, and nitrous oxide. Further preferably, the flow rate of silane is controlled to be 800 - 2000 sccm, the flow rate of the hydrogen gas mixture carrying phosphine is 50 - 1000 sccm, and the flow rate of nitrous oxide is 100 - 2500 sccm. The gradient change can vary within this range.
[0055] During the deposition of the phosphorus-doped and oxygen-doped amorphous silicon layer, the gradient change of at least one of the introduced gases means that, for example, when the introduced gases include silane, a hydrogen gas mixture carrying phosphine, and nitrous oxide, the flow rates of two of the gases can remain unchanged while the flow rate of one gas changes in steps; or the flow rate of one gas remains unchanged while the flow rates of two gases change in steps; or the flow rates of all three gases change in steps.
[0056] In some preferred embodiments of the present invention, in the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer, the flow rates of silane and nitrous oxide are controlled to be unchanged, and the flow rate of the hydrogen gas mixture carrying phosphine changes in a gradient and increases. More preferably, the increasing amplitude is 50 - 200 sccm, which is more conducive to forming a good passivation effect on the silicon wafer surface.
[0057] Further preferably, the number of gradient changes in the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer is at least 3 times, more preferably 3 - 5 times, for example, it can be 3 times, 4 times, or 5 times. Forming the phosphorus-doped and oxygen-doped amorphous silicon layer with the preferred number of gradients is more conducive to improving the bonding force between bonds in the film layer and improving the quality of the film layer.
[0058] Further preferably, in the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer, the flow rate of the hydrogen gas mixture carrying phosphine is changed to the corresponding gradient change value every time a thickness of 0.5 - 2 nm is deposited, which is more conducive to ensuring the stability of passivation and improving the LID resistance of the film layer.
[0059] In the continuous coating process of the present invention, the doping between the film thicknesses corresponding to different gradients of the same film layer is continuously transitional. Because during the process of changing the doping concentration, the gas flow rate is gradually increased from the flow rate of the previous layer to the set flow rate. Therefore, the doping in the transition region changes continuously. For example, when setting the phosphine doping flow rate with three gradients, in the conventional discontinuous coating method, the flow rate of a certain gas for each layer is a fixed value of 20 sccm, 40 sccm, and 60 sccm respectively, and there are inflation and evacuation actions between different gradients; while in the continuous coating method, the flow rate of each layer changes from 0 - 20 sccm and finally stabilizes at 20 sccm; changes from 20 - 40 sccm and finally stabilizes at 40 sccm, and changes from 40 - 60 sccm and finally stabilizes at 60 sccm; the flow rate in the transition region changes continuously from 0 - 20 sccm, 20 - 40 sccm, and 40 - 60 sccm. There is no need for inflation and evacuation actions between different gradients, and there is no need to restart the glow discharge, enabling a natural transition state to be formed between the film thicknesses corresponding to different gradients. The bond binding force between the film thicknesses corresponding to different gradients is better, the film layer quality is better, and it has better anti-LID attenuation performance.
[0060] In some preferred embodiments of the present invention, the phosphorus doping concentration range in the phosphorus-doped and oxygen-doped amorphous silicon layer is from 1×10 19 cm -3 -9×10 20 cm -3 , and the oxygen doping concentration range is from 1×10 18 cm -3 -9×10 19 cm -3 . The phosphorus-doped and oxygen-doped amorphous silicon layer doped with appropriate elements is more conducive to ensuring passivation while improving the anti-LID attenuation performance of the film layer.
[0061] In some preferred embodiments of the present invention, the antireflection layer is at least one of silicon nitride, oxygen-doped silicon nitride, and carbon-doped silicon nitride.
[0062] In some preferred embodiments of the present invention, the antireflection layer includes carbon-doped silicon nitride. The formation of carbon-doped silicon nitride includes a step of continuous coating by using at least one gradient change in the gas introduced under the continuous presence of glow plasma. Here, at least one gradient change in the gas introduced makes the refractive index of carbon-doped silicon nitride gradually decrease from the inside to the outside. The carbon-doped silicon nitride is coated continuously, which is beneficial to improving the denseness and corrosion resistance of the film layer, and is beneficial to taking into account the anti-corrosion performance and optical performance.
[0063] The carbon-doped silicon nitride is also formed by continuous coating, that is, there is no air extraction between corresponding layers with different gradients, and the change between layers is achieved by controlling at least one gradient change in the introduced gas; for example, in the formation of carbon-doped silicon nitride, the introduced gas includes silane, ammonia, and methane. Specifically, the flow rates of two of the gases can be kept constant, and the flow rate of one gas can change stepwise, or the flow rate of one gas can be kept constant, and the flow rates of two gases can change stepwise, or the flow rates of all three gases can change stepwise.
[0064] In some preferred embodiments of the present invention, in the formation of carbon-doped silicon nitride, the introduced gas includes silane, ammonia, and methane. During this process, the flow rate of silane is kept constant, and the flow rates of ammonia and methane change stepwise respectively.
[0065] Further preferably, in the formation of carbon-doped silicon nitride, it is satisfied that: the flow rates of ammonia and methane change once every deposition of 20 - 40 nm in thickness. The increasing change range of the ammonia flow rate is 1000 - 2000 sccm, and the increasing change range of the methane flow rate is 50 - 150 sccm, more preferably 50 - 130 sccm. The increasing change range means adding the corresponding increasing change range to the flow rate of the previous gradient. Exemplarily, when the increasing change range of the ammonia flow rate is 1000 sccm, the ammonia flow rate changes stepwise in sequence as the initial flow rate, the initial flow rate + 1000 sccm, and so on, changing in a 1000 sccm gradient. Adopting this preferred scheme is more conducive to ensuring the antireflection effect and the anti-LID attenuation effect of the film layer.
[0066] Further preferably, in the formation of carbon-doped silicon nitride, it is satisfied that: the initial flow rate range of ammonia is 6000 - 8000 sccm, and the initial flow rate range of methane is 0 - 100 sccm. Adopting this preferred scheme is more conducive to ensuring the passivation and anti-LID attenuation performance of the film layer.
[0067] In some preferred embodiments of the present invention, the carbon doping concentration in carbon-doped silicon nitride is 1×10 19 cm -3 -9×10 21 cm -3 、more preferably 1×10 19 cm -3 -4×10 21 cm -3 ,and the nitrogen doping concentration is 1×10 19 cm -3 -9×10 21 cm -3 。
[0068] Preferably, in the present invention, the refractive index change range of carbon-doped silicon nitride is 1.5 - 2.1, which is more conducive to the antireflection effect of the front film layer.
[0069] In some preferred embodiments of the present invention, the carbon-doped silicon nitride is deposited by a tube-type PECVD method. Further preferably, the deposition conditions of the carbon-doped silicon nitride include: controlling the deposition temperature to be 350 - 600 °C, the deposition pressure to be 1300 - 2500 mtorr, and the power to be 5 kw - 20 kw.
[0070] In some preferred embodiments of the present invention, the gases introduced during the formation of the carbon-doped silicon nitride include silane, ammonia, and methane. The flow rate of silane is 800 - 2000 sccm, the flow rate of ammonia is 6000 - 15000 sccm, and the flow rate of methane is 20 - 1000 sccm, preferably 100 - 1000 sccm.
[0071] In some preferred embodiments of the present invention, the thickness of the carbon-doped silicon nitride is 80 - 160 nm.
[0072] Preferably in the present invention, the thickness ratio of the carbon-doped silicon nitride to the phosphorus-doped and oxygen-doped amorphous silicon layer is (5.3 - 53.3):1, preferably (5.3 - 11.0):1. Adopting the preferred scheme of the present invention is more conducive to improving the passivation of the film layer while taking into account the good antireflection effect.
[0073] In some preferred embodiments of the present invention, the preparation method further includes: forming a mask layer after forming the first semiconductor layer on the backlight side of the silicon wafer, and then forming the second semiconductor opening region; and selecting whether to remove the mask layer outside the second semiconductor opening region on the backlight side of the silicon wafer according to requirements in the final cleaning step of the texturing and cleaning. The type and thickness of the mask layer can refer to the prior art respectively. Exemplarily, the mask layer is at least one of silicon nitride, silicon oxide, silicon oxynitride, or nitrogen-containing polysilicon, and the thickness of the mask layer is 50 - 100 nm.
[0074] The preparation method of the present invention further includes a step of double-sided polishing the silicon wafer before forming the first semiconductor layer on the backlight side of the silicon wafer.
[0075] In some preferred embodiments of the present invention, the preparation method further includes: cleaning the second semiconductor opening region after forming the antireflection layer, which is more conducive to improving the passivation effect of the second semiconductor layer.
[0076] Further preferably, the method for cleaning the second semiconductor opening region includes performing a cleaning treatment with a hydrofluoric acid solution. The mass concentration of hydrofluoric acid in the hydrofluoric acid solution is 1% - 10%. The conditions for the cleaning treatment include: the treatment temperature is 20 °C - 30 °C, and the cleaning time is 30 - 200 s.
[0077] In some preferred embodiments of the present invention, the preparation method may further include other conventional steps, for example, it may include: Then depositing a second semiconductor layer on the back surface; Performing a second etching operation on a portion of the second semiconductor layer on the back side of the silicon wafer to form a first semiconductor opening region spaced apart from the second semiconductor opening region; depositing a conductive film layer on the resulting back surface; Performing a third etching opening on a portion of the conductive film layer located between the first semiconductor opening region and the second semiconductor opening region to form an isolation trench; Metal electrodes are respectively formed on the outer surfaces of the conductive film layers corresponding to the areas where the first semiconductor opening region and the second semiconductor opening region are located.
[0078] Further preferably, the first semiconductor layer includes a first passivation layer and a first doped silicon layer disposed in sequence, and the second semiconductor layer includes a second passivation layer and a second doped silicon layer disposed in sequence, the first passivation layer and the second passivation layer are each independently a tunneling oxide layer or an intrinsic silicon layer, and the first doped silicon layer and the second doped silicon layer are each independently polycrystalline silicon, amorphous silicon, or microcrystalline silicon. One of the first doped silicon layer and the second doped silicon layer is N-type, and the other is P-type.
[0079] In a preferred embodiment of the present invention, the first semiconductor layer comprises a tunneling oxide layer and a first doped polycrystalline silicon layer, arranged in sequence. The second semiconductor layer comprises an intrinsic silicon layer and a second doped silicon layer, arranged in sequence. The intrinsic silicon layer is preferably an intrinsic amorphous silicon layer (more preferably an intrinsic hydrogenated amorphous silicon layer), and the second doped silicon layer is amorphous silicon or microcrystalline silicon. In this preferred embodiment, the present invention utilizes a combined passivation structure, combined with a front-side structure formed using a specific method, to further enhance cell conversion efficiency.
[0080] The thickness and corresponding doping concentration of the tunnel oxide layer or intrinsic silicon layer, the first doped polysilicon layer, and the second doped silicon layer of the present invention can refer to the range of the prior art and can be used in the present invention. For example, the thickness of the tunnel oxide layer is 1-2nm, the thickness of the intrinsic silicon layer is 5-15nm; the thickness of the second doped silicon layer is 7-45nm, and the effective doping concentration is 2e18cm -3 -3e20cm -3 The thickness of the first doped polysilicon layer is 80-150nm, and the effective doping concentration is greater than 5e18cm -3 .
[0081] In a second aspect, the present invention provides a back-contact cell with LID resistance, produced by the method for producing a back-contact cell with LID resistance described in the first aspect. The back-contact cell of the present invention achieves both good LID resistance and excellent passivation, thereby improving cell efficiency.
[0082] The embodiments of the present invention are described in detail below, which are exemplary and only used to explain the present invention, and are not to be construed as limiting the present invention.
[0083] Example 1 A back-contact battery has a structure as shown in Figure 3 and is fabricated by the following method: S1. Double-side polish a silicon wafer 1 (N-type single-crystalline silicon wafer).
[0084] S2. Form a first semiconductor layer and a mask layer on the back side of the silicon wafer 1: The first semiconductor layer includes a tunneling silicon oxide layer 2 and an N-type doped polysilicon layer 3. The mask layer is silicon nitride. The thickness of the tunneling silicon oxide layer 2 is 1.5 nm, the thickness of the N-type doped polysilicon layer 3 is 120 nm, and the effective doping concentration is 9e19 cm -3 , and the thickness of the mask layer is 80 nm.
[0085] S3. Etch an opening on the back side of the silicon wafer 1 for the first time to form a second semiconductor opening region W2; S4. Texturize and clean the front and back opening regions of the above silicon wafer 1. During the texturing process of the front side, the silicon nitride mask layer on the back side of the silicon wafer is also removed by the final cleaning solution; S5. Form a passivation layer and an antireflection layer 6 on the front side of the silicon wafer 1: The passivation layer is a combination of a dense oxide layer 51 and a phosphorus-doped and oxygen-doped amorphous silicon layer 52 arranged in sequence; The thickness of the dense oxide layer 51 is 1.0 nm, which is formed by ozone oxidation combined with hydrogen plasma treatment. Specifically, the ozone oxidation temperature is 200 °C. In the ALD equipment, the ozone flow rate in the first stage is 1500 sccm, the ozone introduction time is 8 s, and then the chamber and pipelines are purged with nitrogen; in the second stage, the ozone flow rate is 4000 sccm, the ozone introduction time is 12 s, and then the chamber and pipelines are purged with nitrogen; in the third stage, the ozone flow rate is 5000 sccm, the ozone introduction time is 15 s, and then the chamber and pipelines are purged with nitrogen.
[0086] After oxidation, hydrogen plasma treatment is carried out. Specifically, a tube-type PECVD equipment is used. The treatment temperature is 460 °C. During the treatment, the hydrogen flow rate is 7000 sccm, the deposition pressure is 1500 mtorr, and the power is 10 kw; the treatment time is 40 s.
[0087] The thickness of the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 9 nm. It is deposited using a tube PECVD equipment. The deposition temperature is 460 °C, the deposition pressure is 1500 mtorr, and the power is 10 kw. During deposition, the flow rate of silane is 1600 sccm, the flow rate of nitrous oxide is 800 sccm, and the flow rate of the hydrogen mixture carrying phosphine (2% phosphine mixed with 98% hydrogen by volume) varies in the range of 50 - 250 sccm. In the present invention, during deposition, the silane and nitrous oxide gases remain unchanged, and the flow rate of phosphine increases in a fixed gradient of 50 sccm, changing once per 1 nm thickness. That is, when depositing from 0 - 1 nm thickness, the phosphine flow rate is set to 50 sccm. Since glow coating starts without waiting for the gas to stabilize, the phosphine flow rate will increase from 0 - 50 sccm until it stabilizes at 50 sccm. When depositing from 1 - 2 nm thickness, the phosphine flow rate is set to 100 sccm, and the phosphine flow rate will increase from 50 - 100 sccm until it stabilizes at 100 sccm. When depositing from 2 - 3 nm thickness, the phosphine flow rate is set to 150 sccm, and the phosphine flow rate will increase from 100 - 150 sccm until it stabilizes at 150 sccm. When depositing from 3 - 4 nm thickness, the phosphine flow rate is set to 200 sccm, and the phosphine flow rate will increase from 150 - 200 sccm until it stabilizes at 200 sccm. When depositing from 4 - 5 nm thickness, the phosphine flow rate is set to 250 sccm, and the phosphine flow rate will increase from 200 - 250 sccm until it stabilizes at 250 sccm. This change continues until the thickness reaches 9 nm. The phosphorus doping concentration range in the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 5×10 19 cm -3 -4×10 20 cm -3 , and the oxygen doping concentration is 7.9×10 18 cm -3 . After calculation, the thickness ratio of the dense oxide layer 51 to the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 0.111:1.
[0088] The anti-reflection layer 6 of the present invention is carbon-doped silicon nitride. The carbon-doped silicon nitride is deposited using a PECVD device at a deposition temperature of 460°C, a deposition pressure of 1600 mtorr, and a power of 10 kW. When depositing carbon-doped silicon nitride, the flow rate of silane is 1000 sccm, and the flow rates of ammonia and methane are changed in a gradient. Specifically, the flow rate of silane is kept constant, and the flow rates of ammonia and methane are changed in increments of 30 nm. The initial flow rate of ammonia is 6000 sccm, and the subsequent flow rate is 1500 sccm. The flow rate of the ammonia gas was increased by 6000 sccm, 7500 sccm, and 9000 sccm every 30 nm. The initial flow rate of methane was 50 sccm, and then the flow rate was increased by 100 sccm every 30 nm. The flow rate of methane was increased by 50 sccm, 150 sccm, and 250 sccm, which was divided into three gradient changes. The thickness of the carbon-doped silicon nitride was 90 nm, and the carbon concentration in the carbon-doped silicon nitride ranged from 2.3 × 10 19 cm -3 -1.5×10 21 cm -3 , nitrogen doping concentration ranges from 5.6×10 19 cm -3 -8.9×10 21 cm -3 The refractive index of the carbon-doped silicon nitride decreases gradually from 2.1 to 1.5. Calculation shows that the thickness ratio of the carbon-doped silicon nitride to the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 10:1.
[0089] S6, cleaning the second semiconductor opening region; The second semiconductor open area is cleaned with an HF solution, wherein the HF mass concentration is 2%, the mass percentage of deionized water is the balance, the treatment temperature is 25°C, and the cleaning time is 100s; S7, forming a second semiconductor layer on the back side of the silicon wafer 1; The second semiconductor layer is a stack of an intrinsic hydrogenated amorphous silicon layer 7 with a thickness of 8 nm and a P-type doped amorphous silicon layer 8; the P-type doped amorphous silicon layer 8 has a thickness of 15 nm and an effective doping concentration of 3e19 cm -3 .
[0090] S8, etching an opening on the back side of the silicon wafer 1 for the second time to form a first semiconductor opening region W1; S9, depositing a transparent conductive film layer 9 with a thickness of 60 nm on the back side of the silicon wafer 1; S10, etching an opening on the back side of the silicon wafer 1 for the third time to form an isolation trench W3; after etching, the resistance between the first semiconductor and the second semiconductor is greater than 1 kΩ.
[0091] S11. On the outer surfaces of the corresponding regions outside the first semiconductor opening region W1 and the second semiconductor opening region W2 on the back side of the silicon wafer 1, metal electrodes 10 are respectively formed.
[0092] Example 2 Performed with reference to Example 1, the difference is that in the formation of the dense oxide layer 51, the ozone flow gradient increases in two gradients, that is, two stages, namely, the corresponding third stage of Example 1 is not carried out, and only the first stage and the second stage of ozone oxidation are carried out. After calculation, the thickness ratio of the dense oxide layer 51 to the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 0.0778:1.
[0093] Example 3 Performed with reference to Example 1, the difference is that in the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer 52, the number of gradient changes of the hydrogen mixed gas carrying phosphine is different. Specifically, the last gradient change of the hydrogen mixed gas carrying phosphine flow corresponding to Example 1 is not carried out (that is, it changes according to the change rule of Example 1 until the thickness is 8 nm, and the gradient change at a thickness of 9 nm is not carried out). At this time, the thickness of the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 8 nm. After calculation, the thickness ratio of the carbon-doped silicon nitride to the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 11.25:1.
[0094] Example 4 Performed with reference to Example 1, the difference is that the thickness of the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 11 nm. The corresponding process that needs to be adjusted to meet this thickness is: the thickness of the first layer in Example 1 is increased by 2 times, the other gradient thicknesses remain unchanged, the number of gradient changes remains unchanged, and the flow change amplitude remains unchanged. After calculation, the thickness ratio of the carbon-doped silicon nitride to the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 8.18:1.
[0095] Example 5 Performed with reference to Example 1, the difference is that the flow rates of the inlet gases ammonia and methane of the carbon-doped silicon nitride in the anti-reflection layer 6 always remain unchanged and are 8500 sccm and 200 sccm respectively, and the refractive index of the carbon-doped silicon nitride always remains unchanged and is 2.05. The carbon doping concentration of the carbon-doped silicon nitride is 3.3×10 19 cm -3 , and the nitrogen doping concentration is 8.2×10 19 cm -3 , and the thickness is 100 nm. After calculation, the thickness ratio of the carbon-doped silicon nitride to the phosphorus-doped and oxygen-doped amorphous silicon layer 52 is 11.11:1.
[0096] Example 6 Performed with reference to Example 1, except that the increasing change range of the methane flow rate in the deposition of the carbon-doped silicon nitride layer 6 is different and is 150 sccm. The initial methane flow rate, the number of its changes, and the thickness are the same as those in Example 1. At this time, the refractive index change range of the carbon-doped silicon nitride is 1.75 - 1.98. The carbon doping concentration of the carbon-doped silicon nitride is 2.8×10 20 -5.6×10 21 cm -3 。
[0097] Comparative Example 1 Performed with reference to Example 1, except that the dense oxide layer 51 is not provided, but the phosphorus-doped and oxygen-doped amorphous silicon layer 52 of Example 1 is directly deposited on the light-receiving surface.
[0098] Comparative Example 2 Performed with reference to Example 1, except that in the formation of the dense oxide layer 51, the ozone flow rate does not increase, but the ozone flow rate remains constant at 1000 sccm and the ozone introduction time remains unchanged.
[0099] Comparative Example 3 Performed with reference to Example 1, except that the deposition of the phosphorus-doped and oxygen-doped amorphous silicon layer 52 does not adopt the continuous coating method, but adopts the conventional method of intermittent glow with air extraction and air intake respectively between different gradient film thicknesses: specifically, after each gradient changes to the preset value and glow coating is carried out to the target thickness, glow end air extraction is carried out, and then air is introduced to stabilize the air pressure to the preset value corresponding to the next gradient change for glow coating to the target thickness, and so on in a cycle. This gradient change is the same as that in Example 1.
[0100] Test Example The back contact batteries obtained in the above examples and comparative examples were subjected to performance tests, and the results are shown in Table 1. Among them, the test method for the anti-LID attenuation ratio is as follows: Using a halogen lamp, the light intensity is set to 1000 W / m², simulating the standard solar spectrum, and continuously illuminating for 96 hours. The power attenuation ratio of the battery before and after the cumulative irradiance is evaluated to determine the light attenuation. The attenuation ratio is (the power of the battery before the cumulative irradiance - the power of the battery after the cumulative irradiance) / the power of the battery before the cumulative irradiance. The smaller the attenuation ratio before and after LID, the stronger the LID anti-attenuation ability and the higher the battery stability.
[0101] The test method for the acid-resistant thickness difference is as follows: The absolute value of the difference in thickness before and after the battery with the film layer structure is infiltrated with a 5 wt% HF solution at room temperature for 120 s is called the anti-corrosion thickness difference, which characterizes the anti-corrosion performance.
[0102] Table 1
[0103] From the above results, it can be seen that compared with the comparative example, adopting the embodiment scheme of the present invention can improve the anti-LID attenuation performance of the battery, effectively improve the overall passivation level and battery efficiency at the same time, and has a high short-circuit current, which is beneficial to improving the anti-corrosion performance and optical performance of the battery.
[0104] Furthermore, according to Embodiment 1 and Embodiments 2-6, it can be seen that adopting the preferred scheme of the present invention is more conducive to improving the anti-LID attenuation performance of the battery, and effectively improving the overall passivation level and battery efficiency at the same time.
[0105] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.
Claims
1. A preparation method of a back-contact battery resistant to LID effect, comprising: A first semiconductor layer is formed on the backlight side of the silicon wafer, and then the first semiconductor layer is etched to form second semiconductor opening regions distributed at intervals; Then, texturing cleaning is performed to form a textured surface on the light-receiving side of the silicon wafer and in the second semiconductor opening regions; thereafter, a passivation layer and an antireflection layer are sequentially formed on the light-receiving side of the silicon wafer. It is characterized in that the passivation layer includes a dense oxide layer and a phosphorus-doped and oxygen-doped amorphous silicon layer formed in sequence; Among them, the formation of the dense oxide layer includes the steps of first oxidizing with a gradually increasing ozone flow rate and then performing hydrogen plasma treatment; The formation of the phosphorus-doped and oxygen-doped amorphous silicon layer includes the step of continuously depositing by at least one of the gases changing in gradient in the presence of a glow plasma, where at least one of the gases changing in gradient makes the phosphorus doping concentration in the phosphorus-doped and oxygen-doped amorphous silicon layer gradually increase from the inside to the outside.
2. The preparation method of the back-contact battery with anti-LID effect according to claim 1, characterized in that, The thickness of the dense oxide layer is 0.5 - 2.5 nm, and the thickness of the phosphorus-doped and oxygen-doped amorphous silicon layer is 3 - 15 nm; and / or, The thickness ratio of the dense oxide layer to the phosphorus-doped and oxygen-doped amorphous silicon layer is (0.03 - 0.83):
1.
3. The preparation method of the back-contact battery with anti-LID effect according to claim 1, characterized in that, In the dense oxide layer, the ozone flow rate gradient increasing oxidation adopts atomic layer deposition, and the oxidation temperature is controlled at 150 - 300 °C; and / or, In the dense oxide layer, the hydrogen plasma treatment adopts tube-type PECVD, and the treatment temperature of the hydrogen plasma treatment is controlled at 350 - 600 °C.
4. The method for preparing a back-contact cell with anti-LID effect according to claim 1 or 3, characterized in that, The ozone flow rate gradient increasing in the formation of the dense oxide layer includes at least three gradients of increase: the ozone flow rate F1 in the first gradient is 1000 sccm - 3000 sccm, the ozone flow rate F2 in the second gradient is 3000 sccm - 5000 sccm, the ozone flow rate F3 in the third gradient is 4000 sccm - 6000 sccm, and F1 < F2 < F3.
5. The preparation method of the back contact battery with anti-LID effect according to claim 4, characterized in that, The ozone introduction time in the first gradient is 5 - 10 s, the ozone introduction time in the second gradient is 10 - 15 s, and the ozone introduction time in the third gradient is 10 - 15 s; and / or, In the formation of the dense oxide layer, the ozone flow rate gradient increasing further includes: purging the chamber and pipeline with nitrogen after the corresponding oxidation in each gradient.
6. The preparation method of the back contact battery with anti-LID effect according to claim 1 or 3, characterized in that The conditions of the hydrogen plasma treatment include: The flow rate of hydrogen is 5000 - 15000 sccm, and the treatment time is 5 - 60 s; and / or, The deposition pressure is 1300 - 2500 mtorr, and the power is 5 kw - 20 kw.
7. The preparation method of the back contact battery with anti-LID effect according to claim 1, characterized in that, The formation of the phosphorus-doped and oxygen-doped amorphous silicon layer adopts tube-type PECVD, where, the deposition temperature is controlled at 350 - 600 °C; and / or, the deposition pressure is controlled at 1300 - 2500 mtorr and the power is 5 kw - 20 kw.
8. The method for preparing a back contact cell with anti-LID effect according to claim 1 or 7, characterized in that, The gases introduced in the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer include silane, a hydrogen mixture carrying phosphine, and nitrous oxide. The flow rate of silane is 800 - 2000 sccm, the flow rate of the hydrogen mixture carrying phosphine is 50 - 1000 sccm, and the flow rate of nitrous oxide is 100 - 2500 sccm.
9. The preparation method of the back-contact cell with anti-LID effect according to claim 8, characterized in that, In the formation of the phosphorus-doped and oxygen-doped amorphous silicon layer, the flow rates of silane and nitrous oxide are controlled to be constant, the flow rate of the hydrogen mixture carrying phosphine changes in gradient and increases, and the increasing amplitude is 50 - 200 sccm; among them, The number of gradient changes is at least 3 times, and / or, the flow rate of the hydrogen mixed gas with phosphine is changed to the corresponding gradient change value every 0.5 - 2 nm thickness deposition.
10. The preparation method of the back-contact battery with anti-LID effect according to claim 1, characterized in that, The phosphorus doping concentration range in the phosphorus-doped and oxygen-doped amorphous silicon layer is from 1×10 19 cm -3 -9×10 20 cm -3 , and the oxygen doping concentration range is from 1×10 18 cm -3 -9×10 19 cm -3 ; And / or, the anti-reflection layer is at least one of silicon nitride, oxygen-doped silicon nitride, and carbon-doped silicon nitride.
11. The preparation method of the back contact battery with anti-LID effect according to claim 1, characterized in that, The anti-reflection layer includes carbon-doped silicon nitride. The formation of carbon-doped silicon nitride includes the step of continuous film deposition by using at least one gradient change in the gas introduced under the continuous presence of glow plasma, where at least one gradient change in the gas introduced makes the refractive index of the carbon-doped silicon nitride gradually decrease from the inside to the outside.
12. The preparation method of the back-contact battery with anti-LID effect according to claim 11, characterized in that, The carbon doping concentration in carbon-doped silicon nitride is 1×10 19 cm -3 -9×10 21 cm -3 ; the nitrogen doping concentration is 1×10 19 cm -3 -9×10 21 cm -3 ; And / or, the refractive index change range of the carbon-doped silicon nitride is 1.5 - 2.
1.
13. The preparation method of the back contact battery with anti-LID effect according to claim 11, characterized in that, The carbon-doped silicon nitride is deposited by the tube PECVD method, and the deposition conditions include: controlling the deposition temperature to be 350 - 600 °C, the deposition pressure to be 1300 - 2500 mtorr, and the power to be 5 kw - 20 kw; And / or, the gases introduced during the formation of the carbon-doped silicon nitride include silane, ammonia, and methane. The flow rate of silane is 800 - 2000 sccm, the flow rate of ammonia is 6000 - 15000 sccm, and the flow rate of methane is 20 - 1000 sccm.
14. The method for preparing a back-contact cell with anti-LID effect according to claim 11 or 13, characterized in that, The gases introduced during the formation of the carbon-doped silicon nitride include silane, ammonia, and methane. During this period, the flow rate of silane is controlled to be constant, and the flow rates of ammonia and methane change in gradients respectively and satisfy: The flow rates of ammonia and methane change once every 20 - 40 nm thickness deposition. The increasing change range of the ammonia flow rate is 1000 - 2000 sccm, and the increasing change range of the methane flow rate is 50 - 150 sccm; And / or, The initial flow rate range of ammonia is 6000 - 8000 sccm, and the initial flow rate range of methane is 0 - 100 sccm.
15. The method for preparing a back contact battery with anti-LID effect according to claim 11 or 12, characterized in that, The thickness of the carbon-doped silicon nitride is 80 - 160 nm, and / or, the thickness ratio of the carbon-doped silicon nitride to the phosphorus-doped and oxygen-doped amorphous silicon layer is (5.3 - 53.3) :
1.
16. The preparation method of the back-contact battery with anti-LID effect according to claim 1, characterized in that, The preparation method further includes: After forming the first semiconductor layer on the backlight side of the silicon wafer, a mask layer is further formed, and then the second semiconductor opening region is formed; and in the final cleaning step of the texturing and cleaning, it is selected whether to remove the mask layer outside the second semiconductor opening region on the backlight side of the silicon wafer according to requirements; After forming the anti-reflection layer, the second semiconductor opening region is cleaned; Then, the second semiconductor layer is deposited on the back; A second etching opening is performed on a part of the second semiconductor layer on the back of the silicon wafer to form a first semiconductor opening region arranged at intervals with the second semiconductor opening region; A conductive film layer is deposited on the obtained back; A third etching opening is performed on a part of the conductive film layer located between the first semiconductor opening region and the second semiconductor opening region to form an isolation groove; Metal electrodes are respectively formed on the outer surfaces of the conductive film layers corresponding to the regions where the first semiconductor opening region and the second semiconductor opening region are located; Among them, the first semiconductor layer includes a first passivation layer and a first doped silicon layer arranged in sequence, the second semiconductor layer includes a second passivation layer and a second doped silicon layer arranged in sequence, the first passivation layer and the second passivation layer are independently a tunneling oxide layer or an intrinsic silicon layer, and the first doped silicon layer and the second doped silicon layer are independently polycrystalline silicon, amorphous silicon, or microcrystalline silicon.
17. A back-contact battery resistant to LID effect, characterized in that, It is obtained by the method for preparing a back-contact cell with anti-LID effect according to any one of claims 1-16.
Citation Information
Patent Citations
Method for depositing multi-layered layers and / or gradient layers
CN102686769A
Solar cell and method for manufacturing same
CN102804394A
Back contact battery with specific front passivation structure and preparation method and application thereof
CN117577697A
Preparation method of heterojunction cell P-type amorphous silicon thin film, thin film and application
CN118048620A
Advanced hydrogenation of silicon solar cells
EP2852986A1